Topical issues of management of public-private partnership in Republic of Kazakhstan - Kirdasinova, K.A.; Abenov, E.M.; Braycheva, T.V. (BUKETOV BUSINESS REVIEW, 2018)
At the present stage of the economic development of the Republic of Kazakhstan, mutually beneficial cooperation of state bodies and entrepreneurs in the sectors traditionally attributed to the state responsibility on the basis of a balanced distribution of risks, benefits and costs, rights and obligations defined in the relevant contracts is quite attractive niche for research. In this regard, the authors of the article carried out a research in the study of topical issues, from the point of view of modern management in the study of public-private partnership. The authors of the article have identified the need and characteristic features that make it possible to single out partnership as an independent economic category. Authors draw a parallel of economic and legal aspects of functioning of state bodies and entrepreneurs in solving key issues. The article substantiates the fact that the partnership between the state and business is a positive development in the country’s economy. Conceptually, it is shown that, within the framework of public-private partnership, each form of cooperation has its own specific features, in particular, in matters of property, which requires an individual approach to each individual link. A number of normative and legislative documents, recently adopted in Kazakhstan for supporting and developing entrepreneurial activity, have been also considered. In results of the research problematic issues were identified, including that it was revealed that institutional changes are required in the process of interaction between the state and business.